2009
DOI: 10.1007/s11085-009-9145-2
|View full text |Cite
|
Sign up to set email alerts
|

The High Temperature Oxidation Behavior of Mg–Gd–Y–Zr Alloy

Abstract: The oxidation behavior of pure Mg and Mg-Gd-Y-Zr alloy was studied in O 2 at 300°C with and without the presence of water vapor. The kinetics curves revealed improved oxidation resistance of Mg-Gd-Y-Zr alloy in O 2 , compared with pure Mg. However, when water vapor co-existed with oxygen, the oxidation rate of Mg-Gd-Y-Zr alloy was accelerated; whereas, the oxidation rate of pure Mg was restrained. Detailed XPS analysis of pure Mg oxidized with water vapor revealed that the reduced oxidation rate could be stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Because Mg-Y-Gd based alloys showed a high specific strength at both room and elevated temperatures [149], the study of Gd on oxidation was focused on Y-containing alloys. Liu et al [150] studied the solid-state oxidation behaviour of an Mg-Gd-Y-Zr alloy within the temperature range from 230 to 300 C in both O2 and O2 + H2O atmospheres. Gd and Y-containing Mg alloys showed low oxidation rates and negligible oxidation weight gains after 10 hour exposure in both atmospheres.…”
Section: Gdmentioning
confidence: 99%
“…Because Mg-Y-Gd based alloys showed a high specific strength at both room and elevated temperatures [149], the study of Gd on oxidation was focused on Y-containing alloys. Liu et al [150] studied the solid-state oxidation behaviour of an Mg-Gd-Y-Zr alloy within the temperature range from 230 to 300 C in both O2 and O2 + H2O atmospheres. Gd and Y-containing Mg alloys showed low oxidation rates and negligible oxidation weight gains after 10 hour exposure in both atmospheres.…”
Section: Gdmentioning
confidence: 99%
“…4,5]. However, oxidation behavior studies at elevated temperatures have not been as widely pursued for Mg [6][7][8][9][10][11][12], but are relevant to applications such as automotive powertrain components, for example. The present authors recently demonstrated the feasibility of performing isotopic tracer studies of the film growth mechanism for the immersion of Mg in water, using sequential exposures in D 2 16 O and/or H 2 18 O water and secondary ion mass spectroscopy (SIMS) analysis [13].…”
mentioning
confidence: 99%
“…As aluminum was continually oxidized to form oxide film and oxygen consumed [13], the growth rate of the oxide layer was accelerated and the oxygen partial pressure of melt gradually decreased, the ability of [Si] oxidized was weakened, so the rate of Si burning slowed down gradually. Because the density of SiO 2 was slightly larger than that of Al, the oxidized SiO 2 was dispersed in the melt and sank slowly with holding time.…”
Section: Analysis and Discussionmentioning
confidence: 99%